2006
DOI: 10.1080/01443610600963846
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors in anaemia in pregnancy at booking in Lagos, Nigeria

Abstract: Anaemia in pregnancy is a common problem in many developing countries. In Nigeria, it is responsible for 11.0% of maternal deaths. This study examined the sociodemographic factors associated with anaemia in pregnancy. Anaemia was defined as a haemoglobin (Hb) level <11 g/dl. Proportions were compared using the chi2 test. A total of 35.3% of the 374 women studied were anaemic. Anaemia was more common in primigravidae than in parous women of parity 2 - 4 (chi2 = 6.87; p = 0.0087). Low socioeconomic status, (chi2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
78
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(113 citation statements)
references
References 13 publications
21
78
5
2
Order By: Relevance
“…10 In our study, just about a third of the patients were aware of analgesia in labour. This level of awareness about pain relief in labour is higher than those from previous studies conducted in other parts of Africa and Asia but much lower than those reported from developed countries were rates as high as 80% have been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In our study, just about a third of the patients were aware of analgesia in labour. This level of awareness about pain relief in labour is higher than those from previous studies conducted in other parts of Africa and Asia but much lower than those reported from developed countries were rates as high as 80% have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…1 The desirability of analgesia in labour in this study is high and similar to reports from other studies. 7,8,10 Since this study consisted of only parous women who had undergone vaginal delivery, with just a small proportion having received some form of pain relief, they must have appreciated the severity of labour pains and may not want to experience such again. In addition, most of the women were well educated and this study confirmed a positive association between maternal educational level and pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Jn 2006, Anorlu's study in Nigeria found that socio-economic status was significantly associated with anemia (p < 0.0001) with higher prevalence among women of low socioeconomic status [22]. The survey in Mauritania revealed that the percentage of anemic subjects is slightly higher among women who do not work (50.2%) than among women who work (46.8%) [23]. In 2013, Bayebie in Dakar found that economic activity reduced the risk of anemia [17].…”
Section: T Jean Augustin Diégane Et Al Open Journal Of Obstetrics Amentioning
confidence: 99%
“…6,7 In developing countries, pregnancy related under nutrition can be attributed to various socioeconomical reasons and poor awareness of basic nutritional requirements. 8 A number of studies have been done previously on correlating maternal anaemia with various socioeconomic groups which were Colomer et al [1990], 9 Bentley and Griffiths [2003], 10 Dairo et al (2004), 11 Anorlu et al (2006). 12 Noronha et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…8 A number of studies have been done previously on correlating maternal anaemia with various socioeconomic groups which were Colomer et al [1990], 9 Bentley and Griffiths [2003], 10 Dairo et al (2004), 11 Anorlu et al (2006). 12 Noronha et al (2010). 13 All of them concluded in their studies that the high prevalence of maternal anaemia was strongly associated with low socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%